Exploring the Antioxidant and Anti-proliferative Effects of Murraya koenigii (L.) Leaves Methanol Extract on T47D Breast Cancer Cell Lines - Nisa, Mutia Khoirun; Salamah, Rohmi; Wijayanti, Nastiti (GHMJ (Global Health Management Journal), 2025)
Background: Murraya koenigii (Curry) leaves are herbal plants that have bioactive compounds such as phenolics, flavonoids, and alkaloids that function as antioxidants and anti-cancers. Aims: This study aimed to quantitatively determine the bioactive compounds in curry leaves by calculating phenolic, flavonoid, and alkaloid content. Its potential as an antioxidant and anti-proliferative compound in T47D breast cancer cell lines was also analyzed. Methods: Murraya koenigii leaves extract was obtained by maceration using 80% methanol (1:5 w/v), then the antioxidant and anti-proliferative test was carried out using the 1,1-Diphenyl-2-Pycrylhidracyl (DPPH) and MTT (-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl tetrazolium bromide) assay, respectively, followed by flow cytometry to determine the apoptotic activity of the extract on T47D breast cancer cell lines. Results: The results for the bioactive compounds in the methanol extract of Murraya koenigii leaves were 156.62±1.49 mg/g phenolics, 99.19±0.25 mg/g flavonoids, and 2.90±0.01 mg/g alkaloids. The IC50 value for antioxidant activity was 25.058±2.2 μg/ml and showed an anti-proliferative effect on T47D cells in a dose-dependent manner with IC50 74.71±5.45 μg/ml for cytotoxicity. Furthermore, flow cytometry showed that a concentration of 1/16 IC50 has the best results for apoptosis. Conclusion: The methanol extract of Murraya koenigii leaves has the potential as an antioxidant and anti-proliferative agent and can induce apoptosis of T47D cells.